(untitled) (Al-Academy, 2025)
The actor is one of the most important elements of dramatic work in visual discourse, whether in theater, cinema, or television. The challenges facing the actor in deserving the title of "actor" and establishing his or her distinctive mark require him or her to pursue their skills, intellect, and physical preparation, as well as their relationship with the script, the director, and the audience. This is particularly true in cinema and television, the subject of this study. Although some directors prioritize directing over the actor, placing him or her in second place, the actor remains an important element in the artistic work, and his or her skill and mental, vocal, and physical effort are what qualify him or her to be a professional actor. While many experts in the field and theory have addressed the study of the art of acting and the methodological approaches to guiding actors to achieve mastery and influence at the same time, there is no material to be read or taught that would enable those who desire to be both actors and creatives at the same time. There is no magic antidote to enable actors to achieve a state of "creativity," to be creative, and to pull them out of the "stereotypical" performance. Even academic study prepares and provides opportunities to enter this profession, and the actor is tasked with thinking about constructing and formulating their expressive means, which require continuous mental, physical, and vocal effort. Academic study teaches you how to use a weapon, but it does not teach you how to hit the target. The researcher believes that the classification of a professional actor can be divided into two categories: The first: the creative, who draws themselves into the realm of the character and the text. The second: the imitator, who draws the text into their personal realm.